Laundering practices and stain removal techniques of selected online ukay-ukay businesses in relation to selected buyers’ expectations - Quero, Irish Joyce F.
This descriptive study analyzed the present laundering practices and stain removal techniques of selected online ukay-ukay businesses in relation to buyers’ expectations. The study randomly selected 17 sellers and 59 buyers as participants. Data were collected through surveys and analyzed using descriptive statistics and thematic analysis. Findings indicate that the primary motivation of sellers in laundering is sanitation and presentability. Similarly, their primary motivation in stain removal is presentability. Handwashing is identified as the most common mode of laundering. Sellers often skip pre-wash garment care practices such as following care labels, making repairs, and turning clothes inside out while optional practices such as bleaching, conditioning and ironing, are often performed to increase product value. Soaking in detergent and bleach is identified as the most common stain removal technique. Other techniques include spot treatment and scrubbing using a brush. The primary problem encountered by sellers in laundering and stain removal is its timeconsuming and labor-intensive nature, which they manage through patience and perseverance. Buyers consider receiving laundered ukay-ukay clothes as highly important and many are willing to pay more for washed, fragrant, and stain-free items. Despite laundering and stain removal efforts of sellers, some buyers still receive clothes with damages, often undisclosed by the seller. The study reveals some misalignment between seller practices and buyer expectations. It recommends implementation of stricter quality control, and practice of full disclosure and transparency at all times to improve service and increase customer satisfaction.